Policía, derecho administrativo e inmigración en Colombia - Malagón Pinzón, Miguel Alejandro (2023)
This article focuses on one of the most important subjects in administrative law in Colombia during the nineteenth century: immigration. In the period of the Liberal Party‘s radicals, and influenced by the German concept of the Police Science, the aims of public administration in Colombia were to colonize the territory through foreigners and to achieve economic development.